Receiving more, expecting less? Social ties, clientelism and the poor's expectations of future service provision. (October 2022) - Jöst, Prisca; Lust, Ellen
Highlights: Poor voters have lower expectations over candidates who provide monetary handouts than those who do not. Poor voters in socially dense communities are more likely than those in less dense communities to witness campaign handouts. In less dense communities, poor voters view candidates who do not provide handouts as more likely to provide future services. Poor voters in dense communities do not expect candidates who only campaign as being more likely to provide services in the future. Poor voters appear to understand electoral handouts more as part of a one-shot exchange than a signal of future services. Abstract: Do citizens expect candidates who hand out goods at election time to provide services once they take office? The literature provides competing views of the relationship between electoral handouts and service provision. One sees handouts as pre-payment for the vote in lieu of future services; the second understands them as signaling the candidate's ability to provide future services. In this paper, we examine how electoral handouts may affect expectations of future service provision. We focus on the poor because they are most dependent on such service provision, and on expectations because they are more easily identified and are likely to reflect past experience. We argue the density of social ties within the community should moderate the relationship between candidates' campaign handouts and expectations of future services. We test this argument using hierarchical models to analyze observational and experimental data from over 14, 000 poor Kenyans, Malawians, and Zambians in 631 communities. We find that respondents generally view monetary handouts to be in lieu of future services. However, we also find important differences in communities with more and less dense social ties. Vote-buying is more common and seen as more acceptable in socially dense than in less dense communities. Respondents from socially dense communities are also less likely to expect future service provision; however, they do not see candidates who give handouts as significantly less likely to provide services than those who do not. Indeed, there is evidence that not providing handouts in these communities may signal the candidate's inability to provide services. These findings highlight the importance of considering how communities' social density affects expectations over service provision and the need to consider, more broadly, how social context affects the distributive consequences of clientelism.